INDUKSI KALUS PADI (Oryza sativa L.) VARIETAS IR64, MENTIK WANGI DAN ROJOLELE MELALUI KULTUR IN VITRO - Rahabistara Sumadji, Angga (Widya Warta, 2015)
Rice (Oryza sativa L.) is a very important food crops because rice is still consumed as a staple food for most of the people all over the world, especially Asia. This study aims to determinethe right concentration of growth regulating substances 2.4-D + BA that can be used to induce the emergence of callus from rice seed and to determine the effect of growth regulating substances on the growth of rice callus IR64, Mentik Wangi, and Rojolele. This study made use of a completely randomized design (CRD), by the addition of growth regulating substances 2.4-D + BA with 0; 0.5; 1; and 2 mg/l level for each. Rice seed varieties used areIR64, Mentik Wangi, and Rojolele. Each treatment was done with three replications. The data were analyzed using descriptive method. The results showed that the concentration of growthregulating substances which could most rapidly induce the emergence of callus with good color and texture was medium with the concentration of 2.4-D 2 mg/l + BA 2 mg/l and theconcentration of 2.4-D 0.5 mg/l + BA 2 mg/l. Rice seed explants were forming callus fastest in 9 days after the planting time. The effect of growth media formulations of 2.4-D + BA wasthat they could produce callus of a crumb texture (friable) in golden brown with the highest callus fresh weight of 21.7 g.